2021
DOI: 10.21103/article11(4)_oa25
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Assessment of Stress and its Relationship with Neuroendocrine Mechanisms of its Development in Obstetricians-Gynecologists against the Background of Professional Burnout

Abstract: The purpose of this сase-control study was to investigate the factors of subjective assessment of stress and their relationship with neuroendocrine mechanisms of its development in obstetricians-gynecologists against the background of professional burnout. Methods and Results: A total of 96 physicians and nurses from the different clinics specializing in both obstetrics and gynecology were surveyed. The Russian versions of MBI, BDI, SF-12, FFMQ, MAAS, and Coping strategies (the Ways of Coping Checklist) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…In this study, a high level of burnout was not associated with the place and the nature of work. However, in our previous research, we also found no dependence of burnout on these sociodemographic factors [30]. We attributed this finding to the effect of coping, which was not taken into account in other studies.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In this study, a high level of burnout was not associated with the place and the nature of work. However, in our previous research, we also found no dependence of burnout on these sociodemographic factors [30]. We attributed this finding to the effect of coping, which was not taken into account in other studies.…”
Section: Discussioncontrasting
confidence: 56%
“…The present study is a successor to the previous research on various aspects of burnout in medical workers employed in obstetrics and gynecology in the Siberian region [30]. Now, we conducted the first large-scale study in the Siberian region examining the features of a healthy lifestyle that prevent burnout in obstetrics and gynecology physicians and nurses.…”
Section: Discussionmentioning
confidence: 84%